Digitalization of the service sector in Russia: Specific Features and Prospects - Lyudmila Mikhailovna KORNILOVA; Anna Sergeevna KORNILOVA (Communications of International Proceedings, 2021)
The rampant development of the society and the needs of the population makes it necessary to expand the range and improve the quality of services provided. In order to ensure the competitiveness of service organizations, the innovations and digitalization processes that penetrate into all sectors become essential. The issues of the digital economy in Russia at the state level were raised at the end of 2016, when the President noted in his message the urgent need to form a new Internet economy in order to increase the efficiency of its industries due to the use of information and communication technologies. In 2017, the Government developed and approved the Digital Economy program in July. The article considers the processes of digital transformation of the service sector in Russia, the features and prospects of digitalization of this sector. It is proved that during digitalization of service activities, the new opportunities arise for consumers of services, the time for servicing customers is reduced, which as a result increases the availability and quality of services.
Keywords: digital economy; digitalization; information and communication technologies; service sector